Reformasi Islam Dunia Melayu-Indonesia: Studi Pemikiran, Gerakan, dan Pengaruh Muḥammad Thāhir Jalāl al-Dīn - Mafri Amir (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2008)
This article shows the role of Malay’s figure, Muhammad Thāhir Jalāluddin, in the growth of reform and movement of Islam renewal in Indonesia in the early 20th century. Traceable opinion of Thāhir at least in its influence colouring a number of printed media and education institution was exist in that moment.